Możliwości integracji analizy strategicznej z procesem planowania finansowego - Kąkol, Wiesław (Possibility of Integration Strategic Analysis with Financial Planning Process, 2008)
The financial planning in turbulent environments is a very difficult task. A lot of appearing and disappearing factors makes the deep analysis of external surroundings and interior of an enterprise necessary. Building financial plans should start with the strategic analysis process. The available information gives a view on the relationship among financial positions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 254-262